Zachowania konsumenckie w handlu na przykładzie miasta Bolesławiec - Adamczuk, Franciszek (Consumer behaviour in trade on the example of Bolesławiec town, 2005)
The article concerns consumers behaviour in trade in Bolesławiec town. The elaboration is a result of research which has been conducted between 2003 and 2004, on the background of the town’s trade function. In the end of the elaboration are estimations of the problem and conclusions which can be used in forming trade function of Bolesławiec town in the future. The author used available literature and scientific research on this subject.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 230-240